Absolute Proper Motions Outside the Plane (APOP). Issue Volume 8:Issue S293(2012) (29th April 2014) - Qi, Zhaoxiang; Yu, Yong; Smart, Richard L.; Lattanzi, Mario G.; Tang, Zhenghong; Bucciarelli, Beatrice; Vecchiato, Alberto; Spagna, Alessandro; McLean, Brian J.
Abstract: Most of the discovered exoplanets are close to our sun. Usually their host star is with large proper motions, which is an important parameter for exoplanet searching. The first version of absolute proper motions catalog achieved based on Digitized Sky Survey Schmidt plate where outside the galactic plane | b |≥27° is presented, resulting in a zero point error less than ± 0.3 mas/yr, and the overall accuracy better than ± 4.5 mas/yr for objects brighter than R F =18.5, and ranging from 4.5 to 9.0 mas/yr for objects with magnitude 18.5< R F <20.5. The systematic errors of absolute proper motions related to the position, magnitude and color are practically all removed. The sky cover of this catalog is 22, 525 degree 2, the mean density is 6444 objects/ degree 2 and the magnitude limit is around R F =20.5.